Flexible labor market and the precariat work of foreign staff in Iceland - Skaptadóttir, Unnur Dís; Wojtyńska, Anna (School of Social Sciences, 2023)
In the last decades, the number of foreign citizens has grown in Icelandic labour market. Many of them have arrived to work in low income jobs in the growing tourism sector, in construction, production and care work. Indirect hiring through staffing agencies and service companies have become more common in Iceland than before. The goal of this article is to highlight the working conditions of these workers. The discussion is based on an ethnographic study, which included interviews with individuals with special knowledge of the topic because of their work experiences. The study shows that they have witnessed changes in the labour market which indicate a deteriorating position of foreign workers. The current diverse hiring practices make it difficult for the unions to check the potential breaking of the labour laws. Á síðustu áratugum hefur erlendu fólki fjölgað mikið á íslenskum vinnumarkaði. Stór hluti þess hefur komið til að vinna í láglaunastörfum í vaxandi ferðaþjónustu, í byggingariðnaði og framleiðslu- og umönnunarstörfum. Ráðningum í gegnum ráðningar- og þjónustufyrirtæki hefur fjölgað. Markmið þessarar greinar er að varpa ljósi á stöðu erlends láglaunafólks á íslenskum vinnumarkaði. Umfjöllunin byggir á etnógrafískri rannsókn sem felur meðal annars í sér viðtöl við einstaklinga sem hafa þekkingu á þessum málum vegna starfa sinna. Helstu niðurstöður leiða í ljós að viðmælendur upplifa miklar breytingar á vinnumarkaði sem felast meðal annars í að brot á réttindum erlends starfsfólks eru algengari en áður. Jafnframt er erfiðara fyrir verkalýðsfélög en áður að hafa eftirlit með brotunum vegna mismunandi ráðningarforma.